Distribution of Hauled-Out Ladoga Ringed Seals (Pusa hispida ladogensis) in Spring 2012 - Trukhanova, Irina S.; Gurarie, Eliezer; Sagitov, Rustam A. (ARCTIC, 2013)
The spatial distribution and habitat selection of the Ladoga ringed seal (Pusa hispida ladogensis), an endangered freshwater seal, are poorly understood, particularly for the ice-covered period. A fixed-wing, strip-transect aerial survey conducted in early April 2012, before the Lake Ladoga breakup, provided data on seal density and distribution throughout the lake in relation to several environmental covariates: depth, distance to shore, recreational ice-fishing activity, and ice type. A predictive model was applied to combinations of covariates to estimate the total number of seals hauled out on ice of Lake Ladoga. The model estimate was 5068 (95% CI: 4026 – 7086) seals over an area of 16 827 km2. The mean observed seal density was 0.29 seals/km2 (SD = 0.351, range from 0 to 8.61), and density was highest (> 1 seal/km2) in regions that were relatively shallow (< 50 m). Densities appeared to increase with distance from shore but dropped off again at the longest distances. The average density was lower in fast ice habitats (0.13 seals/km2) than in drifting pack ice habitats (0.44 seals/km2). Relatively high seal densities observed in “ice edge” zones (0.26 seals/km2) could be explained by the ice formation pattern of large ridged and hummocked areas in the transition zone between shorefast ice and secondary ice. The presence of fishermen had a highly significant negative effect on seal presence (β = −7.8, p = 0.0014), resulting in a nearly twofold decrease in seal density in shorefast ice habitats (0.09 seals/km2 in fishing areas and 0.15 seals/km2 in areas without fishing activity). An extensive winter recreational fishery, in combination with potential negative trends in ice conditions on the lake, might reduce the amount of suitable habitat for the Ladoga ringed seal in the near future. La répartition spatiale et la sélection de l’habitat du phoque marbré de Ladoga (Pusa hispida ladogensis), phoque d’eau douce en voie de disparition, ne sont pas bien comprises, surtout en ce qui a trait à la période ...